Correlation of Resting Heart Rate with the Severity and Complexity of Coronary Artery Disease: A Single-Center Retrospective Study - Demir, Vahit (Int J Prev Med, 2019)
BACKGROUND: We aimed to explore the association between resting heart rate (RHR) and the severity and complexity of atherosclerosis in coronary artery disease (CAD). METHODS: Clinical and laboratory data of 388 patients who underwent coronary angiography were evaluated retrospectively. SYNTAX and Gensini scores were calculated based on angiographic findings. These scores which indicate the severity of atherosclerosis was calculated for all the patients. Patients were divided into three main groups according to RHR. Group 1 composed of patients with RHR ≤70 (n = 217), group 2 composed of patients with RHR between 70 and 89 (n = 133), and group 3 composed of patients with RHR ≥90 beats per min (bpm) (n = 38). Gensini and SYNTAX score values of the three study groups were compared. Also, Gensini score was tested for whether it showed a positive correlation with RHR and SYNTAX scores. RESULTS: All patients had an average age of 61.3 years, and the mean for RHR was 72 bpm. Mean Gensini score in the general CAD population was 24.4 ± 22.5, and mean SYNTAX score was 13.6 ± 8.1 points. The Gensini and Syntax score values of the group 3 were significantly higher than that of the other two groups (59.8 ± 31.2, P < 0.001 and 26.0 ± 6.5, P < 0.001, respectively). There was a significant correlation with Gensini score and RHR, SYNTAX score, C-reactive protein (CRP), and left ventricular ejection fraction [(r = 0.725, P < 0.001), (r = 0.680, P < 0.001), (r = 0.543, P < 0.001), (r = −0.224, P < 0.001), respectively]. CONCLUSIONS: RHR is an effective easily available marker for the assessment of severity and complexity of CAD.